2020
DOI: 10.3390/nu12113490
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Profile of Orthorexic Behavior and “Normal” Eating Behavior with Cluster Analysis: A Cross-Sectional Study among Polish Adults

Abstract: Although the amount of research about orthorexia nervosa (ON) has grown in the last two decades, to date, research on ON remains inconsistent. More is known about some behavioral characteristics of ON and its prevalence but nothing is known about the profile analysis behind this pathological eating behavior maintenance. Therefore, the objective of the present study was to determine the profiles of the participants in terms of eating behaviors, eating disorder psychopathology, obsessive-compulsive disorder symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Furthermore, this correlation was relatively low, thus supporting the discriminant validity of the I-DOS. Low but signi cant correlation coe cient was also found between I-DOS and the severity of obsessive and compulsive symptoms measured by OCI-R total [27], consistently with previous evidence [47]. This nding reveals that the two conditions may have similar cognitive and behavioral characteristics, as some authors suggest [48].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, this correlation was relatively low, thus supporting the discriminant validity of the I-DOS. Low but signi cant correlation coe cient was also found between I-DOS and the severity of obsessive and compulsive symptoms measured by OCI-R total [27], consistently with previous evidence [47]. This nding reveals that the two conditions may have similar cognitive and behavioral characteristics, as some authors suggest [48].…”
Section: Discussionsupporting
confidence: 88%
“…5 School of Pharmacy, Lebanese International University, Beirut, Lebanon. 6 Life Sciences and Health Department, Paris-Est University, Paris, France. 7 Faculty of Medicine and Medical Sciences, Holy Spirit University of Kaslik (USEK), Jounieh, Lebanon.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Despite its adverse effects, ON is not included as an eating disorder in the Diagnostic and Statistical Manual of Mental Disorders-5th edition (DSM-5) as of now [4]. Several diagnostic criteria of ON overlap with symptoms of other psychological disorders [2], such as obsessive-compulsive disorder (OCD) [5,6] and Anorexia Nervosa (AN) [7], triggering discussions about its categorical classification [8]. Having said that, the essence differs between ON and AN: the main concern for orthorexic eating behaviors are health and purity while the core of AN is weight loss and food quantity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Higher TOS scores were found in females compared to males. Despite the fact that no or small gender differences were found between male and female groups regarding ON tendency rates [ 30 , 56 , 57 ], many ON-related studies revealed the same problem as our sampling scheme, where females are more represented than males (76.1% of our participants are females) [ 58 , 59 ]. However, aside from ON, disordered eating in general was found to be more susceptible in Lebanese female adolescents where concerns for healthy body image are of a higher grade than in male Lebanese adolescents [ 60 ].…”
Section: Discussionmentioning
confidence: 99%